SEARCH FOR HEAVY NEUTRAL LEPTONS IN E+E- ANNIHILATIONS AT 29 GEV - Errede, D; Akerlof, C; Chapman, J; Harnew, N; Kesten, P; Kooijman, S; Meyer, D; Nitz, D; Rubin, D; Seidl, A; Thun, R; Trinko, T; et al. (1984)
A search was made in 29 GeV e+e- annihilations for heavy, neutral leptons decaying to e±X∓(ν), where X is a muon or charged meson. Six events with isolated e±X∓ pairs were found for an intergrated luminosity of 106 pb-1. The expected background is 5.5 ± 2.2 events. Limits on σ s ̇B depend on mass and range from 8 to 20 × 10-5 nb. © 1984.